ABSENSI KEHADIRAN MENGGUNAKAN OPTICAL FINGERPRINT BERBASIS NodeMCU ESP32 - Alfarizal, Niksen; Amperawan, Amperawan; Rasyad, Sabilal; Uswa, Khoirotun; Nuranisah, Mourinda (Jurnal Ampere, 2021)
Fingerprint sensor or fingerprint sensor is one technology that is still quite reliable because it is proven to be relatively accurate, safe, and comfortable to use as input data when compared to other biometric systems. The design of the attendance attendance system using an ESP-based optical fingerprint serves as an interface to store incoming data and outgoing data when doing attendance, the attendance attendance system using an optical fingerprint is designed to facilitate processes that have been done manually so far can be replaced by attendance using a fingerprint that is more accurate and has good security. . the main component of the sensor used is the fingerprint sensor as fingerprint input, RTC DS137 for storing time and date, an indicator of the success of attendance attendance will be displayed on the LCD as a text display stating the success of attendance or failure and the data will be directly displayed and data storage uses RAMABSTRAKSensor finger Print atau sensor sidik jari merupakan salah satu teknologi yang masih cukup handal karena terbukti relative akurat, aman, dan nyaman untuk dipakai sebagai input data bila dibandingkan pada system biometric yang lainnya. Perancangan system absensi kehadiran menggunakan optical fingerprint berbasis ESP  berfungsi sebagai interface untuk menyimpan  data  masuk data keluar  saat melakukan absensi, system absensi kehadiran menggunakan optical fingerprint dirancang untuk memudahkan proses yang  selama ini dilakukan secara manual dapat digantikan oleh  absensi  menggunakan fingerprint lebih akurat dan keaman yang baik. komponen utama sensor yang digunakan  sensor fingerprint sebagaiinput sidik jari, RTC DS137  untuk penyimpan waktu dan tanggal,  indikator keberhasilan absensi kehadiran akan ditampilkan padaLCD sebagai tampilan teks yang menyatakan keberhasilan absensi atau gagal serta data akan langsung ditampilkan dan penyimpan data menggunakan RAM.